THE EXPERIENCE OF PENETRATING KERATOPLASTY IN INFANTS WITH CONGENITAL CORNEAL OPACITIES - A. V. Pleskova; E. V. Mazanova (Офтальмохирургия, 2017)
Background. Corneal opacity (CO) in children is a severe pathology. In most cases it is characterized by a combination of leucoma with various pathologies of the entire anterior segment of the eye (microcornea, microphthalmia, cataract, adhesion of the lens with the corneal endothelium, glaucoma, atrophy of the iris, often partial or total aniridia). Congenital malformations of other organs and systems are supplements of the clinical pattern. A single method of treatment is penetrating keratoplasty (PK). For all its radicalism and with its entire curative potential, the majority of ophthalmic surgeons prefer to refuse corneal transplantation in children, and transfer it to a later period, particularly in babies aged less one year.Purpose. To evaluate the early and long-term results of penetrating keratoplasty (PKP) n children operated on the 1st year of life for congenital corneal opacities CCO.Material and methods. All patients were divided into 2 groups. The first group consisted of children with CCO, who underwent the PKP, the second group – children with CCO, where limbokeratoplasty was performed. In the first group results of 42 PKP with cadaver corneas were taken for the analysis carried out in 40 children on 42 eyes, in the second group: results of penetrating limbokeratoplasty were taken for the analysis in 8 children (8 eyes) aged from 2 to 12 months for the period 20082014. The average age was 7.2±2.1. The results of the PKP in 40 children (42 eyes) operated on in infancy were compared with the results of the PKP in 22 children who underwent the surgery for the same reason (CCO) aged over 1 year. The functional outcome was assessed roughly: according to the tracking toys by children looking at a certain distance and using the method of the preferred gaze.Results. In the first group in a comparative aspect the biological results of the PKP in newborns were slightly worse than those in older children (65% and 81%, respectively). At the same time, the functional results in case of an early (under one year) CCO treatment exceeded those that were in the postponed treatment (over one year). If in the children operated on in infancy, satisfactory results after the PKP were observed in a half of the cases, in the children operated at an older age – only in 1 case out of10. In the second group (corneal staphyloma) only 1 of 8 transplanted grafts retained the transparency one year after limbokeratoplasty, the organ-preserving result was achieved in all cases.Conclusion. Under certain conditions (a hard selection of patients for the surgery, a sparing microsurgical technique, a careful postoperative monitoring of the condition of the eyes, a timely treatment of complications) the surgical treatment of CCO in the early stages can be quite successful.